A protective effect of inflammatory bowel disease on the severity of sclerosing cholangitis - Stumme, Friederike; Steffens, Niklas; Steglich, Babett; Mathies, Franziska; Nawrocki, Mikolaj; Sabihi, Morsal; Soukou-Wargalla, Shiwa; Göke, Emilia; Kempski, Jan; Fründt, Thorben; Weidemann, Sören; Schramm, Christoph; et al. (Frontiers in Immunology, 2024)
Background: Primary sclerosing cholangitis (PSC) is a chronic liver disease marked by inflammation of the bile ducts and results in the development of strictures and fibrosis. A robust clinical correlation exists between PSC and inflammatory bowel disease (IBD). At present, published data are controversial, and it is yet unclear whether IBD drives or attenuates PSC. Methods: Mdr2-deficient mice or DDC-fed mice were used as experimental models for sclerosing cholangitis. Additionally, colitis was induced in mice with experimental sclerosing cholangitis, either through infection with Citrobacter rodentium or by feeding with DSS. Lastly, fibrosis levels were determined through FibroScan analysis in people with PSC and PSC-IBD. Results: Using two distinct experimental models of colitis and two models of sclerosing cholangitis, we found that colitis does not aggravate liver pathology, but rather reduces liver inflammation and liver fibrosis. Likewise, people with PSC-IBD have decreased liver fibrosis compared to those with PSC alone. Conclusions: We found evidence that intestinal inflammation attenuates liver pathology. This study serves as a basis for further research on the pathogenesis of PSC and PSC-IBD, as well as the molecular mechanism responsible for the protective effect of IBD on PSC development. This study could lead to the discovery of novel therapeutic targets for PSC.